A green and facile method to fabricate superhydrophobic coatings. (4th May 2019) - Huang, Yanfen; Lv, Zaosheng; Cao, Zhe; Huang, Chi
ABSTRACT: In this work, we reported a green and facile method to fabricate superhydrophobic coatings via blending TiO2 nanoparticles and fluorinated acrylate copolymers. The fluorinated acrylate copolymers were synthesised with the method of solution polymerisation using ethanol as solvent. The integration of TiO2 nanoparticles and the fluorinated acrylate copolymers satisfied two necessary conditions of multi-scale nano/microstructures and low surface energy for fabricating superhydrophobic coatings. It was found that the water contact angle and contact angle hysteresis of the as-prepared coatings were respectively 156.3° and 3.7°, and it indicated that the coatings had excellent superhydrophobicity and self-cleaning ability. In particular, these coatings showed good thermal stabilities. Owing to its flexibility, simplicity and non-toxicity, the method is not only a facile and inexpensive way to achieve the lotus effect but could also create coatings with high values in practical application.